Deposição de sílica e teor de nitrogênio e silício em arroz - Mauad, Munir; Crusciol, Carlos Alexandre Costa [UNESP]; Grassi Filho, Hélio [UNESP]; Machado, Silvia Rodrigues [UNESP] (Universidade Estadual de Londrina, 2013)
The nitrogen fertilization is an important practice to reach high productivity, however, nitrogen high level can cause lodging and make the plants more sensitive to disease. Numerous studies has demonstrate that a lot of grasses accumulate silicon at its tissues, and the biggest part of this element is deposited on the leaf, that would work like a mechanical barrier to diseases come in. However, high levels of nitrogen can reduce the silica deposition at the plants. The objective of this study was to evaluate silicon and nitrogen content in shoot and silica deposition in upland rice leaf as a result of Si and N levels. The experimental design used was completely randomized in factorial schema 3 x 2 with five replications. The treatments consisted from levels of N (5, 75 and 150 mg dm-3 of soil) in urea form and two levels of SiO2 (0 e 400 mg dm-3) in calcium silicate form (Wollastonita). The increased of urea fertilization reduced the silicon content of rice plants and the silica deposition at the external cells wall the epidermal rice leafs.
Silica deposition and rate the nitrogen is silicon in rice
Keywords: Fertilization; Oryza sativa; Vegetation anatomy